تقييم فعالية استخدام الوسائط المتعددة (Multimedia) في تبسيط مفاهيم الجغرافيا لدى طلاب المرحلة الجامعية (Comprehensive Journal of Science, 2025)
This study aims to evaluate the impact of employing multimedia (interactive images, digital maps, educational videos, and 3D models) on enhancing undergraduate students' understanding of geographical concepts compared to traditional methods. The study is based on a comparison between two groups: one group that uses multimedia in teaching, Others rely on traditional methods (text-based lectures and books). Pre-test and post-test assessment tools were used to determine the extent of improvement in understanding and comprehension after the application of multimedia, in addition to a questionnaire to clarify the technical aspect, the efficiency of time and effort use, and the impact of this on students' academic achievement.Preliminary results showed that using multimedia improves comprehension and increases student engagement with the material, while also reducing the time required to understand complex concepts, compared to traditional methods. These findings are consistent with previous studies that have demonstrated the importance of multimedia in higher education. For example, Mayer’s study (2009) showed that combining images and educational texts increases information retention and improves understanding [1].
Keywords: Multimedia, Geography, PowerPoint, ArcGIS, Camtasia.